A retrospective study of clinical features and outcome in patients with refractory or recurrent hepatoblastoma: A single institution experience - Jen-Yin Hou; Ting-Chi Yeh; Ting-Huan Huang; Jin-Cherng Sheu; Hsi-Che Liu (Pediatrics and Neonatology)
Background: Hepatoblastoma (HB) is the most common childhood primary hepatic malignancy. The overall survival rate in patients with HB has reached more than 80% over the past decades. The poor prognostic and high-risk HB have been defined, but the treatment and cure of refractory or relapsed HB is still an arduous task. Methods: The complete records of HB in patients under the age of 18 at the MacKay Memorial Hospital between 1990 and 2019 were examined. Results: The treatment results for 11 patients with refractory or relapsed HB are presented. The multi-modality treatment records were reviewed and the clinical characteristics associated with poor outcome included multifocal lesions, low α-fetoprotein, great vessel invasion and metastases. Delayed liver tumor surgery was carried out in eight cases. The median duration of follow-up for the 11 patients was 48.6 months (range 1.9 to 316.8 months). The 5-year and 10-year overall survival rate were 62.3% ± 15% (SE) and 49.9% ± 16.4% (SE), respectively. Most treatment-related toxicities were tolerable. The major concern during long term follow-up was irreversible high-frequency hearing loss. Conclusion: Patients with refractory/relapsed HB are still a thorny issue and more research is needed to improve the outcome.